Endophytic bacteria associated with tissue culture and leaves of Plinia peruviana - Queiroz, Eder Gonçalves; Degenhardt, Juliana; Quoirin, Marguerite; Silva, Krisle da (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to isolate endophytic bacteria from tissue culture and leaves of jaboticaba (Plinia peruviana) and to evaluate their potential as plant growth-promoting bacteria. The bacteria were isolated from nodal segments grown in vitro and from leaves from a tree under natural conditions, totaling 11 and 54 isolates, respectively. The isolates were characterized by colony morphology. The indolic compounds produced by the isolates, in the presence or absence of 100 mg L-1 tryptophan, were quantified. The greatest producers of these compounds were identified by sequencing the 16S rRNA gene and were inoculated on jaboticaba seeds, using Azospirillum brasilense (Ab-V6) as a positive control. The sensitivity of bacteria to eight antibiotics was also evaluated. All assessed bacteria produced indolic compounds, especially Bacillus sp., with a content of 27.41 µg mL-1. The germination rate of the seeds inoculated with Stenotrophomonas sp. was high – 97.34% compared with that of 74.67% of the negative control. Bacillus sp. and Stenotrophomonas sp. also sped up germination. Chloramphenicol limited the growth of 82% of the isolates, followed by amoxicillin, gentamicin, levofloxacin, and tetracycline, which limited 70%; erythromycin was only effective against 35%. The endophytic bacteria isolated from jaboticaba show characteristics of plant growth-promoting bacteria, and Bacillus sp. and Stenotrophomonas sp., obtained from tissue culture, are capable of enhancing jaboticaba seed germination.